"After that, I was leery about giving anybody a break about anything": Officer-perceived consequences of trauma exposure on interactions with the public. (July 2021) - Hofer, Meret S.; Guarnera, Lucy A.; Savell, Shannon M.
Abstract: Purpose: The purpose of this study is to examine the ways in which police officers connect their own direct and secondary trauma exposure to negative collateral effects on police-public interactions. Methods: Data are drawn from in-depth, semi-structured interviews with 48 police officers from across the U.S., representing a range of professional and personal backgrounds. Data were examined using a blended inductive/deductive coding strategy. Results: Officers' narratives show that trauma exposure and related deteriorations in mental health are seen as an inevitable part of police work. Officers linked trauma exposure to negative cognitions about the perception of danger, the controllability of events, and the overarching nature of humanity. Finally, officers connected these negative cognitions directly to the frequency and quality of their contact with the public. Specifically, officers described (1) avoidant behaviors including physical and emotional avoidance of situations that could result in further psychological or bodily harm, and (2) approach behaviors including more defensive, hostile and enforcement-based approaches to the public. Conclusions: Findings provide support for a cognitive-behavioral framework to explain the reported effects of police trauma exposure on interactions with the public. Implications for research and practice are discussed. Highlights: Police see trauma exposure and associated mental health problems as inevitable Officers link trauma to negative cognitions about self, others, and the world Negative cognitions lead to avoidant and defensive behaviors with the public. Avoidant behaviors include withdrawal, emotional distancing, and dehumanization. Approach behaviors include more defensive, hostile or enforcement-based approaches.